Recrutamento e seleção de elites partidárias em Sergipe : o caso dos líderes do Partido Verde - Vieira, Bergson Morais (2013)
This dissertation is inserted in thematic studies of political elites. The main objective of this work is to analyze the leaders of the Green Party (PV) in the State of Sergipe, trying to understand, through the analysis of their itineraries, as is the process of recruitment and selection of those who occupy a position of leadership within the party. The central question of the study was to capture the main features used by these leaders in order to allow them access to available positions in the party. It is, therefore, to examine how to combine different resources (social, cultural, professional, economic) regarding access and the rise to positions of leadership in that party. These objectives were achieved from a research agenda established in the "sociology of engagement" in which it was possible to develop a theoretical-methodological strategy that allowed the understanding of the relationship between the social, cultural and accumulated knowledge with access to positions of prominence in college. The methodological procedures adopted for the "construction" of this work were, in addition to data collected by the current literature, primary data collected through interviews with the group considered. The results indicate that we deal with a rather homogeneous as to social resources and professional. Its members, mostly provide the middle and upper classes, and the example of other party elites, professional categories most frequent traders and freelancers traditional (RODRIGUES, 2009). However, some elements also show that dealing with a very specific group devoid of militant and political capital which, to some extent, explains the "success" in a party without a lot of "force" in the Brazilian political system. As a result, the PV is set for a good portion of which are part of the group considered as an important space for socialization political activist.